2015
DOI: 10.1155/2015/917415
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Variation in Rain Use Efficiency in Semiarid Grasslands of Inner Mongolia

Abstract: Rain use efficiency (RUE) is an important indicator for identifying the response of plant production to variation in precipitation patterns, especially in semiarid ecosystem grasslands of Inner Mongolia. We have investigated the response and spatial patterns of RUE to precipitation patterns based on five years (2006, 2007, 2008, 2012, and 2013) of records from semiarid ecosystem sites across Inner Mongolia. Our results showed thatRUEADMwas lowest in the wettest year (2012) and highest in the year following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Grasslands play important roles in both the economy and ecology of the semi-arid region on the Loess Plateau of China, which is one of the most sensitive ecosystems to adapt to the changes in rainfall pattern during the growing season in water-limited regions (Fu et al, 2010;Lee et al, 2014;Bhandari et al, 2015). The construction of artificial grasslands with high regional adaptation was an effective practice to address the problems created by grassland degradation, and it is the key measure to ensure the sustainable development of grasslands in the region (Shan and Xu, 2009;Xu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands play important roles in both the economy and ecology of the semi-arid region on the Loess Plateau of China, which is one of the most sensitive ecosystems to adapt to the changes in rainfall pattern during the growing season in water-limited regions (Fu et al, 2010;Lee et al, 2014;Bhandari et al, 2015). The construction of artificial grasslands with high regional adaptation was an effective practice to address the problems created by grassland degradation, and it is the key measure to ensure the sustainable development of grasslands in the region (Shan and Xu, 2009;Xu et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Rain use efficiency (RUE) is defined as the amount of biomass produced per unit of precipitation and is the key indicator for measuring the response of plant production to precipitation [18]. The RUE provides a useful index for improved understanding of the relationship between precipitation and vegetation productivity, as well as for evaluating the degradation of grasslands [14,[17][18][19]. For example, Sahnoun et al [20] using Modis level 2 G data estimated RUE and determined environmental changes along a spatial gradient of arid lands in Southern Tunisia, and they found that this methodology provided a way to monitor changes in resilience induced by land-use in this arid region, as well as support detection of future desertification.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of RUE in different regions have shown that RUE is affected by many factors such as temperature and precipitation [19,21,22]. For example, Hountondji [23] revealed the changes of RUE in the ongoing desertification process of West Africa and they found that the RUE over 49.5% of the Sahel region was stable, while the area under 38% declined and only 1.3% showed an upward trend during the years between 1982 to 1999.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong relation between rainfall and RUE in that increasing and decreasing of RUE may be in the result of rainfall increasing and decreasing. However, this positive relation doesn't exist in all region because RUE is controlled by several factors such as vegetation composition, soil condition and biogeochemical constraints (Bhandari et al, 2015). Hence, spatial pattern of RUE and effective factors are different from site to site (Jia et al, 2015).…”
Section: Introductionmentioning
confidence: 97%